Improving Learning Outcomes of Learners Using Cooperative Learning Model Three - Step Interview on the Geometry Room in Class XII MIPA 2 SMA Negeri 2 Pekanbaru - Indraningsih, Indraningsih (UIR Press, 2018)
Learning activities in formal education can not be separated from the process of learning activities at school. In order for the learning process goes well, then a teacher in addition to mastering the material, is also required to master the model that can enable learners in the learning process.Successful achievement of educational goals in schools much depends on how the process experienced by learners as learners. The learning process can be done in school, at home, or study guidance.For learning in school, learners are faced with a number of subjects, one of the subjects of mathematics. Mathematics is a compulsory subject accepted by SMA/MA students.Mathematics is a science that studies about the material, natural phenomena and mechanisms that occur in it. More simply can be said that math is closely related to daily life. One alternative learning model that is expected to enable learners is cooperative three-step interview technique.Cooperative learning type three-step interview is one type of cooperative learning is quite simple, and can be trained to learners who are not accustomed to follow cooperative learning. Cooperative learning model of three-step interview can help learners to strengthen and master the concept of subject matter.This model gives learners the opportunity to work independently and cooperate with others by exchanging opinions and exchanging information with other learners in their group.According to Lie with the application of three-step intervew model gives at least eight times more chance to each learner to discuss in group.Based on the results obtained the value of the first cycle, the second cycle and the third cycle in a row (82,10%), (83,63%) and (87,16%).